Evaluation of the level of antithrombin in patients with glomerulonephritis and nephrotic syndrome: A cross-sectional study - I. Mykhaloiko; R. Yatsyshyn; I. Dudar; H. Kuryliv (Український Журнал Нефрології та Діалізу)
The present study aimed to evaluate the level of antithrombin (AT)-III in blood serum in patients with primary glomerulonephritis (GN) and nephrotic syndrome (NS) and to assess its correlation with markers of NS and hypercoagulation.